Humor processing and its relationship with clinical features in patients with first-episode schizophrenia - Yunfei Ji; Bingjie Huang; Jia Huang; Xiaodong Guo; Tianqi Gao; Yue Zheng; Wanheng Hu; Xiaolin Yin; Xianghe Wang; Xin Yu; Chengcheng Pu (Schizophrenia Research: Cognition)
Humor, a higher-order social cognitive process unique to humans, is commonly impaired in patients with chronic schizophrenia. However, humor processing and its association with the clinical characteristics in the early stage of the illness remain unknown. In this study, we investigated humor processing and its relationship with clinical features in patients with first-episode schizophrenia (FES). We recruited 45 patients with FES and 44 healthy controls matched for age, sex, and education level. The participants completed the Picture Humor Processing Task (HPT-p) and Video Humor Processing Task (HPT-v), which evaluated humor comprehension and appreciation, and a questionnaire assessing their humor styles. Clinical participants also completed clinical and social functioning measurements. Signal detection theory analysis was used to calculate the d' and β values, which represent the detection of humor signals in the comprehension phase and inner criteria of the humor appreciation phase, respectively. In the HPT-p, patients with FES showed a higher false alarm rate (p = 0.048) than healthy controls, whereas the hitting rate, signal recognition ability (d' value), and intrinsic evaluation criterion (β value) were comparable between the two participants groups. In the HPT-v, patients with FES showed lower within-group coherence in the funniness rating (p = 0.023) than healthy controls. In addition, the false alarm rate in the HPT-p and negative symptoms effectively predicted social functioning in patients with FES (R2 = 0.681, p < 0.001). Our results indicate that impairment of humor comprehension in patients with schizophrenia is generated in the first episode and contributes to social functioning deficits, which require early recognition and intervention.